AJUBA promotes the proliferation, invasion and migration of NSCLC cells by activating the ERK/β-catenin pathway - Lianyue Qu; Fan Wang; Yuxiang Wang; Zixuan Li (Scientific Reports)
Abstract Accumulating evidence indicates that AJUBA acts as a potential target for new therapeutics to treat cancers. Nevertheless, the role of AJUBA in non-small cell lung cancer (NSCLC) remains unclear. In the current study, immunohistochemistry (IHC) showed that expression of AJUBA was upregulated in 67.55% of NSCLC tumor samples and was associated with tumor size, lymph node metastasis, advanced tumor stage, poor differentiation and poor prognosis. Loss-of-function assays of AJUBA produced by silencing RNA (siAJUBA) significantly inhibited the proliferation, invasion and migration of H1299 and A549 cell lines. Mechanistically, inhibition of extracellular signal-regulated kinases (ERKs) blocked the AJUBA-induced proliferation, invasion and migration of NSCLC cells, and decreased the expression of proteins related to the endothelial-mesenchymal transition (EMT). Silencing of AJUBA repressed tumor growth and led to a decrease in p-ERK, β-catenin and N-cadherin in vivo. In conclusion,, overexpression of AJUBA facilitates the proliferation and motility of NSCLC cells via the ERK and Wnt/β-catenin pathways. AJUBA may be useful as a prognostic marker which may provide a promising approach for the treatment of NSCLC.